Dental Care Utilization and Unmet Dental Needs in Older Korean Americans. (September 2014) - Jang, Yuri; Yoon, Hyunwoo; Park, Nan Sook; Chiriboga, David A.; Kim, Miyong T.
Objective: The study explored predictors of dental care utilization and unmet dental needs in older Korean Americans, considering predisposing, enabling (dental insurance, acculturation, and family network), and need (self-rated oral health) variables.Method: Multivariate regression models were used to evaluate the data from 209 Korean Americans (aged ≥60) surveyed in Central Texas.Results: Participants with strong family networks and fair/poor self-ratings of oral health reported higher numbers of dental visits in the past year. The likelihood of having an unmet dental need increased when participants had less education, a shorter stay in the United States, no dental insurance coverage, lower levels of acculturation, more limited family networks, fair/poor self-ratings of oral health, and fewer numbers of dental visits.Discussion: Our findings underscore the vulnerability of individuals who are culturally and linguistically isolated and lack family resources, and they highlight the importance of incorporating social and cultural factors in intervention efforts.